Clinician perceptions and patient experiences of antiretroviral treatment integration in primary health care clinics, Tshwane, South Africa - Maphuthego D. Mathibe; Stephen J.H. Hendricks; Anne-Marie Bergh (AOSIS, 2015)
Background: Primary Health Care (PHC) clinicians and patients are major role players in the South African antiretroviral treatment programme. Understanding their perceptions and experiences of integrated care and the management of people living with HIV and AIDS in PHC facilities is necessary for successful implementation and sustainability of integration. Objective: This study explored clinician perceptions and patient experiences of integration of antiretroviral treatment in PHC clinics. Method: An exploratory, qualitative study was conducted in four city of Tshwane PHC facilities. Two urban and two rural facilities following different models of integration were included. A self-administered questionnaire with open-ended items was completed by 35 clinicians and four focus group interviews were conducted with HIV-positive patients. The data were coded and categories were grouped into sub-themes and themes. Results: Workload, staff development and support for integration affected clinicians' performance and viewpoints. They perceived promotion of privacy, reduced discrimination and increased access to comprehensive care as benefits of service integration. Delays, poor patient care and patient dissatisfaction were viewed as negative aspects of integration. In three facilities patients were satisfied with integration or semi-integration and felt common queues prevented stigma and discrimination, whilst the reverse was true in the facility with separate services. Single-month issuance of antiretroviral drugs and clinic schedule organisation was viewed negatively, as well as poor staff attitudes, poor communication and long waiting times. Conclusion: Although a fully integrated service model is preferable, aspects that need further attention are management support from health authorities for health facilities, improved working conditions and appropriate staff development opportunities.